2007
DOI: 10.4314/just.v27i2.33035
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sphenocentrum jollyanum Pierre root extract on sexual behaviourand hormonal levels in rodents

Abstract: Roots of S. jollyanum are considered as sexual stimulant in Ghanaian traditional medicine. The present study is aimed at investigating the effect of an ethanolic extract of the root of S. jollyanum on sexual behaviour of male mice and reproductive hormones in male rats. Extract of S. jollyanum (100, 300 and 1000 mg/kg p.o) stimulated mounting and mating behaviour by increasing mounting frequency, intromission frequency and prolonged ejaculation latency. In addition, a decrease in mounting latency, intromission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Traditional uses of different part of S. jollyanum in treatment of various ailments in West Africa Sub-region are common practice (Amidu et al, 2008;Moody et al, 2006). The roots are bright yellow with a sour taste when chewed (Neuwinger, 1996) and are used as 'chewsticks', relief for constipation, as a stomachic, as a cough medicine, for sickle cell disease, rheumatism inflammatory conditions, malaria treatment (Burkill, 1985;Iwu, 1993;Moody et al, 2006), as a central nervous system (CNS) stimulant and for anxiogenic and aphrodisiac in Ghana (Abbiw, 1990;Owiredu et al, 2007;Woode et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Traditional uses of different part of S. jollyanum in treatment of various ailments in West Africa Sub-region are common practice (Amidu et al, 2008;Moody et al, 2006). The roots are bright yellow with a sour taste when chewed (Neuwinger, 1996) and are used as 'chewsticks', relief for constipation, as a stomachic, as a cough medicine, for sickle cell disease, rheumatism inflammatory conditions, malaria treatment (Burkill, 1985;Iwu, 1993;Moody et al, 2006), as a central nervous system (CNS) stimulant and for anxiogenic and aphrodisiac in Ghana (Abbiw, 1990;Owiredu et al, 2007;Woode et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Herbal concoctions for these ailments are sold at every nook and cranny in southwestern Nigeria. Some plants listed here as an aphrodisiac are said to increase the level of testosterone in test organisms in various studies, for example, Spondias mombin has had its folkloric uses supported with pharmacological data [ 107 ] and Sphenocentrum jollyanum [ 108 ]. In a previous study [ 18 ], 209 medicinal plants are reported to be used as an aphrodisiac and sexual dysfunction in sub-Saharan Africa, of which 28 species are from Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…Investigation on the potential of the plant extracts to affect sexual activities and hormonal levels in laboratory animals was carried out by Owiredu et al [ 43 ]. It was observed that there was an increased urge by the male animals to mount on the female for the first time, increased duration of ejaculation, and shortened refractory period.…”
Section: Pharmacological and Biological Activitiesmentioning
confidence: 99%